Fatal injury as a function of rurality- A tale of two Norwegian counties - Bakke, Håkon Kvåle; Hansen, Ingrid Schrøder; Bendixen, Anette Bakkane; Morild, Inge; Lilleng, Peer Kåre; Wisborg, Torben (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2013)
Background Many studies indicate rural location as a separate risk for dying from injuries. For decades, Finnmark, the northernmost and most rural county in Norway, has topped the injury mortality statistics in Norway. The present study is an exploration of the impact of rurality, using a point-by-point comparison to another Norwegian county. Methods We identified all fatalities following injury occurring in Finnmark between 2000 and 2004, and in Hordaland, a mixed rural/urban county in western Norway between 2003 and 2004 using data from the Norwegian Cause of Death Registry. Intoxications and low-energy trauma in patients aged over 64 years were excluded. To assess the effect of a rural locale, Hordaland was divided into a rural and an urban group for comparison. In addition, data from Statistics Norway were analysed. Results Finnmark reported 207 deaths and Hordaland 217 deaths. Finnmark had an injury death rate of 33.1 per 100,000 inhabitants. Urban Hordaland had 18.8 deaths per 100,000 and rural Hordaland 23.7 deaths per 100,000. In Finnmark, more victims were male and were younger than in the other areas. Finnmark and rural Hordaland both had more fatal traffic accidents than urban Hordaland, but fewer non-fatal traffic accidents. Conclusions This study illustrates the disadvantages of the most rural trauma victims and suggests an urban-rural continuum. Rural victims seem to be younger, die mainly at the site of injury, and from road traffic accident injuries. In addition to injury prevention, the extent and possible impact of lay people’s first aid response should be explored.